High-temperature-resistant ceramic fiber board and preparation method thereof
By covering the silicon layer in the surface of the ceramic fiber surface in advance, the problem of difficulty staying in the adhesive is solved, and the adhesive strength and high temperature resistance of the high temperature resistance ceramic fiber plate are significantly improved, and the flame retardant performance and fire burning are achieved. After the strength.
Patent Information
- Application Number
- CN202411450524.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing high-temperature resistant ceramic fiberboards are difficult to retain the adhesive during the preparation process, resulting in poor bonding strength and high-temperature resistant performance.
Through chemical gas sedimentation method, the silicon layer of the gas phase is pre -covered in the ceramic fiber surface, and it uses it to transform into colloidal shape in an alkaline water environment, thereby increasing the retention rate of the adhesive.
The bonding strength and high temperature resistance of the ceramic fiber plate are significantly improved, and the flame retardant performance is good. The strength and hardness before and after the fire remain good.
Smart Images

Figure BDA0005088971700000081 
Figure BDA0005088971700000101
Abstract
Description
Technical Field
[0001] The invention relates to the field of fireproof materials, and in particular to a high-temperature resistant ceramic fiberboard and a preparation method thereof. Background Art
[0002] Ceramic fiberboard is a refractory material that can withstand flame erosion at 1000-1200℃. It has high strength, a certain supporting function, excellent impact resistance, and good thermal insulation performance. Ceramic fiberboard has a wide range of applications. Among them, this material can be used as a fireproof material between battery cells, between battery modules, or between battery boxes and passenger compartments (or energy management systems) in new energy vehicles or energy storage industries. When thermal runaway occurs due to overcharging, puncture, collision, etc., the ceramic fiberboard can effectively block the impact of flames and absorb the huge energy generated by the thermal runaway explosion, thereby preventing the spread of thermal runaway of the battery and ensuring the safety of users' lives and property.
[0003] The existing preparation of high temperature resistant ceramic fiberboard mainly includes the following steps: a) chopping alumina fibers, mixing with pure water and a wet strength agent, and dispersing, then adding alumina powder and inorganic binders such as silica sol to the obtained dispersion, stirring evenly to obtain a mixture; b) pouring a starch aqueous solution into the mixture obtained in step a) for flocculation to obtain a slurry; c) wet vacuum forming the slurry obtained in step b), and drying it to obtain a high temperature resistant ceramic fiberboard.
[0004] As can be seen from the above, the existing high temperature resistant ceramic fiberboard usually uses inorganic adhesives such as silica sol as adhesives. In this way, it is easy to have the problem that silica sol is difficult to stay in the ceramic fiber slurry during the preparation process (liquid silica sol is easily soluble in water and will be lost in large quantities with the aqueous solution), so that the product bonding strength is not as good as expected, and ultimately the flame retardancy, high temperature resistance and physical strength of the product are not ideal. In order to improve the bonding strength of the product, a large amount of organic adhesives such as starch are often used, but this will significantly reduce the flame retardancy of the high temperature resistant ceramic fiberboard, and when burned at high temperature, the organic adhesive will easily produce a large number of holes after being decomposed by heat, resulting in a loose material structure and low impact strength.
[0005] In summary, how to improve the retention rate of adhesives such as silica sol in the preparation process of high-temperature resistant ceramic fiberboards to improve the bonding strength and high-temperature resistance of high-temperature resistant ceramic fiberboards has positive significance. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a high temperature resistant ceramic fiberboard and a preparation method thereof. The present invention uses ceramic fiber coated with a fumed silica layer as the main raw material of the high temperature resistant ceramic fiberboard, which can avoid a large amount of adhesive loss during the preparation process of the high temperature resistant ceramic fiberboard, thereby significantly improving the retention rate of the adhesive, and finally obtaining a high temperature resistant ceramic fiberboard with high bonding strength and high high temperature resistance.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a high temperature resistant ceramic fiberboard, comprising the following raw materials in parts by weight: 30-70 parts of ceramic fiber coated with a gas phase silica layer, 20-50 parts of ceramic filler, 10-30 parts of glass powder, 0.05-1 part of flocculant, and water.
[0008] In the prior art, silica sol is usually difficult to stay in the preparation process of high temperature resistant ceramic fiberboard, and the use of organic adhesives such as starch will lead to a decrease in the flame retardancy and physical strength of the high temperature resistant ceramic fiberboard. To this end, the present invention makes the following improvements: On the one hand, the present invention ingeniously utilizes chemical vapor deposition to pre-wrap fumed silica on the surface of ceramic fibers, and then disperses the ceramic fibers at high speed in an appropriate amount of alkaline aqueous system, so that the fumed silica can be transformed in situ into a viscous colloid in an alkaline water environment. Since the fumed silica is pre-attached to the surface of the ceramic fibers, it remains attached to the surface of the ceramic fibers in a colloid state and will not dissolve or disperse in water in large quantities. This can solve the problem that the ceramic fiber slurry is difficult to stay in the high-temperature resistant ceramic fiberboard because the adhesive is soluble in water in large quantities. The present invention uses fumed silica as an adhesive without adding organic adhesives such as starch, so that the ceramic fiberboard can maintain ultra-high strength and hardness before and after burning, and has very good flame retardant properties.
[0009] On the other hand, the present invention adds a proper amount of ceramic filler and glass powder to the high temperature resistant ceramic fiberboard, so that the high temperature resistant ceramic fiberboard can have a ceramic effect under flame impact, thereby improving the material strength, especially excellent impact resistance.
[0010] Preferably, the fumed silicon dioxide layer is formed by in-situ oxidation of tetraethyl orthosilicate (TEOS) and / or silane (SiHH4) on the surface of the ceramic fiber by chemical vapor deposition.
[0011] Tetraethyl orthosilicate (TEOS) and silane (SiH4) can react in situ on the surface of ceramic fibers in an oxidizing atmosphere to form a fumed silica coating. The reaction principle is as follows: Si(OC2H s )4+O2(gas)→SiO2(solid)+by-product; siH4(gas)+O2(gas)→SiO2(solid)+H2.
[0012] Preferably, the ceramic fiber is one or more of aluminum silicate fiber, aluminum oxide fiber, mullite fiber, quartz fiber, silicon carbide fiber, zirconium oxide fiber and nitride fiber; more preferably, it is high-aluminum aluminum silicate fiber.
[0013] Preferably, the porcelain-forming filler is one or more of wollastonite, diatomaceous earth, kaolin, calcium carbonate and mica powder.
[0014] Preferably, the glass powder is one or more of silicon oxide, boron oxide and metal oxide; wherein the metal oxide is one or more of lead oxide, aluminum oxide, zinc oxide, titanium oxide, magnesium oxide, barium oxide, calcium oxide, tin oxide and antimony oxide.
[0015] Preferably, the flocculant is one or more of polyacrylamide, polyethyleneimine, aluminum sulfate, ferric sulfate and polyaluminum chloride.
[0016] In a second aspect, the present invention provides a method for preparing a high temperature resistant ceramic fiberboard, comprising the following steps: S1: Add water to a ball mill, add ceramic fibers coated with a fumed silica layer to the water, adjust to alkalinity, and disperse at high speed.
[0017] S2: Add porcelain filler and glass powder and mix well.
[0018] S3: Add flocculant and stir slowly until flocs are formed. Flocculation is complete when the solution becomes clear.
[0019] S4: The obtained slurry is poured into a mold for dehydration, and the flocculated ceramic fibers and other powders are left on the mold for forming.
[0020] S5: transferring the obtained molding material to a hot pressing mold and drying it under vacuum pressure to obtain a high temperature resistant ceramic fiberboard.
[0021] In the above S4, the present invention can use molds of different shapes to cooperate with slurry dehydration for integrated molding, and can customize special-shaped high-temperature resistant ceramic fiberboards as needed. For example, when used as a fireproof material for new energy vehicles, the shape can be customized to achieve 360° no-dead-angle protection.
[0022] Preferably, the method for preparing the ceramic fiber having a fumed silica layer coated on the surface comprises: 1) Place the ceramic fiber in a reaction chamber and introduce oxygen.
[0023] 2) Ethyl orthosilicate or silane is introduced into the reaction chamber, and after reaction, it reacts on the surface of the ceramic fiber to form a fumed silicon dioxide layer.
[0024] 3) After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0025] After ethyl orthosilicate is vaporized by heating, ethyl orthosilicate gas or silane gas diffuses to the surface of the ceramic fiber and reacts with oxygen at a certain temperature to generate solid gas-phase silicon dioxide deposited on the surface of the ceramic fiber.
[0026] Furthermore, in step 2), the temperature of the reaction chamber is adjusted to 200-1000°C and the pressure is 10 2 -10 5 Pa; the flow ratio of ethyl orthosilicate or silane to oxygen is 2 / 3-2:1, and the reaction time is 5-30 minutes.
[0027] The present invention finds that in the above reaction, the deposition rate of fumed silicon dioxide increases exponentially with increasing temperature, but after reaching a certain temperature, the deposition rate depends on the concentration of the reaction gas, and too high a temperature increases energy consumption. In addition, the above reaction is mainly carried out under normal pressure or low pressure. Both too short and too long a deposition time will affect the deposition effect.
[0028] Preferably, in S1, the dispersion speed is 1000-3000 r / min, the time is 60-120 min, and the pH value is adjusted to 8-10. Preferably, in S2, the stirring speed is 300-2000 r / min, and the time is 2-10 min.
[0029] Preferably, in S3, the stirring speed is 300-2000 r / min, and the time is 1-5 min.
[0030] Preferably, in S5, the temperature of hot pressing and drying is 120-180° C., and the time is 1-5 min.
[0031] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention ingeniously uses chemical vapor deposition to pre-wrap fumed silica on the surface of ceramic fibers, which can solve the problem that the ceramic fiber slurry is difficult to stay in the high-temperature resistant ceramic fiber board because the binder is dissolved in water in large quantities. In addition, the present invention uses fumed silica as a binder without adding organic binders such as starch, which can enable the ceramic fiber board to maintain ultra-high strength and hardness before and after burning; and has excellent flame retardant properties.
[0032] (2) The present invention adds an appropriate amount of ceramic filler and glass powder to the high temperature resistant ceramic fiberboard, so that the high temperature resistant ceramic fiberboard can have a ceramic effect under flame impact, thereby improving the material strength, especially the excellent impact resistance.
[0033] (3) The high temperature resistant ceramic fiberboard of the present invention is lightweight, has a density below 1 g / cm3, and can be customized in shape according to demand, thereby obtaining a special-shaped high temperature resistant ceramic fiberboard. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with the embodiments.
[0035] Overall embodiment A high temperature resistant ceramic fiberboard comprises the following raw materials in parts by weight: 30-70 parts of ceramic fibers coated with a gas phase silica layer, 20-50 parts of ceramic fillers, 10-30 parts of glass powder, 0.05-1 part of flocculant, and water.
[0036] In some specific implementation cases, the fumed silicon dioxide layer is formed by in-situ oxidation of tetraethyl orthosilicate (TEOS) and / or silane (SiH4) on the surface of the ceramic fiber by chemical vapor deposition.
[0037] In some more preferred implementation cases, the fumed silica layer includes an inner layer of fumed silica and an outer layer of fumed silica; wherein the outer layer of fumed silica is looser and more porous than the inner layer of fumed silica. In order to better combine other powder raw materials with ceramic fibers and between ceramic fibers, inner and outer layers of fumed silica can be deposited on the surface of ceramic fibers. Among them: the inner layer is denser than the outer layer, which can make the combination between the fumed silica layer and the ceramic fibers tighter and reduce the risk of the fumed silica layer falling off; the outer layer is looser and more porous, and the colloid viscosity formed after contacting water is higher, which can better combine other powder raw materials or ceramic fibers with ceramic fibers.
[0038] In some specific implementation cases, the ceramic fiber is one or more of aluminum silicate fiber, aluminum oxide fiber, mullite fiber, quartz fiber, silicon carbide fiber, zirconium oxide fiber and nitride fiber; more preferably, it is high-aluminum aluminum silicate fiber.
[0039] In some specific implementation cases, the porcelain-forming filler is one or more of wollastonite, diatomaceous earth, kaolin, calcium carbonate and mica powder.
[0040] In some specific implementation cases, the glass powder is one or more of silicon oxide, boron oxide and metal oxide; wherein the metal oxide is one or more of lead oxide, aluminum oxide, zinc oxide, titanium oxide, magnesium oxide, barium oxide, calcium oxide, tin oxide and antimony oxide.
[0041] In some specific implementation cases, the flocculant is one or more of polyacrylamide, polyethyleneimine, aluminum sulfate, ferric sulfate and polyaluminum chloride.
[0042] A method for preparing a high temperature resistant ceramic fiberboard comprises the following steps: S1: Add water to a ball mill, add ceramic fibers coated with a fumed silica layer to the water, adjust to alkalinity, and disperse at high speed.
[0043] In some specific implementation cases, in S1, the dispersion speed is 1000-3000 r / min, the time is 60-120 min, and the pH value is adjusted to 8-10.
[0044] S2: Add porcelain filler and glass powder and mix well.
[0045] In some specific implementation cases, in S2, the stirring speed is 300-2000 r / min, and the time is 2-10 min.
[0046] S3: Add flocculant and stir slowly until flocs are formed. Flocculation is complete when the solution becomes clear.
[0047] In some specific implementation cases, in S3, the stirring speed is 300-2000 r / min, and the time is 1-5 min.
[0048] S4: The obtained slurry is poured into a mold for dehydration, and the flocculated ceramic fibers and other powders are left on the mold for forming.
[0049] S5: transferring the obtained molding material to a hot pressing mold and drying it under vacuum pressure to obtain a high temperature resistant ceramic fiberboard.
[0050] In some specific implementation cases, in S5, the temperature of hot pressing and drying is 120-180° C., and the time is 1-5 min.
[0051] In some specific implementation cases, the method for preparing the ceramic fiber having a fumed silica layer coated on the surface includes: 1) Place the ceramic fiber in a reaction chamber and introduce oxygen.
[0052] Furthermore, in step 1), the temperature of the reaction chamber is adjusted to 200-1000°C and the pressure is 10 2 -10 5 Pa.
[0053] 2) Ethyl orthosilicate or silane is introduced into the reaction chamber, reacts with oxygen and then reacts on the surface of the ceramic fiber to form a fumed silicon dioxide layer.
[0054] Furthermore, in step 2), the flow ratio of ethyl orthosilicate or silane to oxygen is 2 / 3-2:1, and the reaction time is 5-30 min.
[0055] 3) After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0056] Further preferably, the method for preparing the ceramic fiber having a fumed silica layer coated on the surface comprises: 1) Place the ceramic fiber in a reaction chamber and introduce oxygen.
[0057] 2) Ethyl orthosilicate and silane are introduced into the reaction chamber at the same time, and the temperature is controlled so that the gaseous silane reacts preferentially to reach the reaction temperature, forming an inner layer of fumed silica on the surface of the ceramic fiber; then the silane is stopped, the temperature is increased and the pressure is reduced to allow the ethyl orthosilicate to react, and an outer layer of fumed silica is formed on the surface of the inner layer of fumed silica. In the above step 2), when the two fumed silica precursors ethyl orthosilicate and silane are introduced into the reaction chamber, due to the temperature control, silane will preferentially undergo an oxidation reaction on the surface of the ceramic fiber to form an inner layer of fumed silica, and the reaction temperature of ethyl orthosilicate and oxygen needs to be above 300°C, so an outer layer of fumed silica can be formed on the surface of the inner layer of fumed silica after heating. The texture and morphology of the inner layer of fumed silica and the outer layer of fumed silica can be achieved by adjusting the ratio of oxygen to the two fumed silica precursors and the pressure. Due to the lower gas pressure and the ratio of TEOS to oxygen concentration, the outer layer of the deposited fumed silica is more loose and porous.
[0058] Further, in step 2), the temperature of the reaction chamber is first adjusted to 200-300°C and the pressure is normal pressure; after stopping the silane flow, the temperature is adjusted to 300-1000°C and the pressure is 10 2 -10 4 The flow ratio of silane to oxygen is 1-2:1, and the reaction time of silane to oxygen is 5-10 min; the flow ratio of ethyl orthosilicate to oxygen is 1 / 2-5 / 6:1, and the reaction time of ethyl orthosilicate to oxygen is 3-7 min.
[0059] 3) After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0060] Specific Examples and Comparative Examples Example 1 (Single-layer fumed silicon dioxide layer) (I) Preparation of ceramic fibers coated with a fumed silica layer by chemical vapor deposition (CVD): S1: Place high-aluminum aluminum silicate ceramic fiber in the reaction chamber of the CVD chamber, introduce oxygen, and adjust the temperature of the reaction chamber to 550° C. and the pressure to normal pressure.
[0061] S2: introducing tetraethyl orthosilicate into the reaction chamber, reacting with oxygen and then reacting on the surface of the ceramic fiber to form a fumed silica layer, wherein the flow ratio of tetraethyl orthosilicate to oxygen is 1:1, and the reaction time is 20 minutes.
[0062] S3: After the reaction is completed, stop introducing gas and return the reaction chamber to atmospheric pressure to end chemical vapor deposition. Then the product can be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a high-aluminum aluminum silicate ceramic fiber with a vapor-phase silica layer on the surface.
[0063] (II) Preparation of high temperature resistant ceramic fiberboard: S1: Add 2000 g of water to a ball mill, add 7 g of ceramic fiber coated with a fumed silica layer, adjust the pH to 9, and disperse at high speed (dispersion speed is 2000 r / min, time is 90 min).
[0064] S2: Add 3.5g of wollastonite as a porcelain filler and 2.0g of glass powder (main components are 62.1wt% silicon oxide, 16wt% boron oxide, 12.5wt% titanium oxide, 8wt% zinc oxide, and 1.4wt% aluminum oxide), and stir evenly (stirring speed is 1000r / min, time is 5min).
[0065] S3: Add 0.05 g of aluminum sulfate as a flocculant and stir evenly (stirring speed is 1000 r / min, time is 3 min).
[0066] S4: pouring the obtained slurry into a mold for dehydration and molding.
[0067] S5: hot pressing and drying the obtained molding material (the pressing and drying temperature is 150° C. and the time is 3 minutes) to obtain a high temperature resistant ceramic fiberboard.
[0068] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that the fumed silica is not pre-coated on the surface of the ceramic fiber, but silica sol is directly added during the preparation of the high temperature resistant ceramic fiber board. The specific preparation steps are as follows: S1: Add 2000g of water into a dispersion tank, then add 3.5g of wollastonite as a porcelain filler, 2.0g of glass powder (main components are 62.1wt% silicon oxide, 16wt% boron oxide, 12.5wt% titanium oxide, 8wt% zinc oxide, and 1.4wt% aluminum oxide), and stir evenly (stirring speed is 1000r / min, time is 5min).
[0069] S2: Add 4g of high-aluminum aluminum silicate ceramic fiber and stir evenly (stirring speed is 1000r / min, time is 5min). S3: Add 7.5g of silica sol aqueous solution (concentration 40wt%) and stir evenly (stirring speed is 1000r / min, time is 5min).
[0070] S4: Add 0.05 g of aluminum sulfate as a flocculant and stir evenly (stirring speed is 1000 r / min, time is 3 min).
[0071] S5: pouring the obtained slurry into a mold for dehydration and molding.
[0072] S6: hot press drying the obtained molding material (the pressing and drying temperature is 150° C. and the time is 3 minutes) to obtain a high temperature resistant ceramic fiberboard.
[0073] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the raw materials do not contain ceramic fillers and glass powder. The specific preparation steps are as follows: (I) Preparation of ceramic fibers coated with a fumed silica layer by chemical vapor deposition (CVD) The same as in Example 1: S1: Place high-aluminum aluminum silicate ceramic fiber in the reaction chamber of the CVD chamber, introduce oxygen, and adjust the temperature of the reaction chamber to 550° C. and the pressure to normal pressure.
[0074] S2: introducing tetraethyl orthosilicate into the reaction chamber, reacting with oxygen and then reacting on the surface of the high-aluminum aluminum silicate ceramic fiber to form a fumed silica layer, wherein the flow ratio of tetraethyl orthosilicate to oxygen is 1:1, and the reaction time is 20 minutes.
[0075] S3: After the reaction is completed, stop introducing gas and return the reaction chamber to atmospheric pressure to end chemical vapor deposition. Then the product can be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a high-aluminum aluminum silicate ceramic fiber with a vapor-phase silica layer on the surface.
[0076] (II) Preparation of high temperature resistant ceramic fiberboard: S1: Add 2000 g of water to a ball mill, add 7 g of ceramic fiber coated with a fumed silica layer, adjust the pH to 9, and disperse at high speed (dispersion speed is 2000 r / min, time is 90 min).
[0077] S2: Add 0.05 g of aluminum sulfate as a flocculant and stir evenly (stirring speed is 1000 r / min, time is 5 min).
[0078] S3: Pour the obtained slurry into a mold for dehydration and molding.
[0079] S4: hot pressing and drying the obtained molding material (the pressing and drying temperature is 150° C. and the time is 3 minutes) to obtain a high temperature resistant ceramic fiberboard.
[0080] Performance Testing The performance of the high temperature resistant ceramic fiberboards prepared in Example 1 and Comparative Examples 1-2 was tested, and the testing method was as follows: (1) Density: GB / T 17911-2018; (2) Tensile strength: GB / T 17911-2018; (3) Impact strength: GB / T 1043-1993; (4) Flame retardant: UL94; (5) Tensile strength after fire: GB / T 17911-2018: Test the tensile strength of the material by burning it at 1000°C for 10 minutes. (6) Impact strength after fire: GB / T 1043-1993: Test the impact strength of materials by burning them at 1000℃ for 10 minutes.
[0081] The test results are shown in the following table: From the comparison of the data in the above table, we can see that: Compared with Comparative Example 1, in Example 1, the fumed silica is pre-coated on the surface of the ceramic fiber, while in Comparative Example 1, the silica sol is directly added to the aqueous solution during the preparation process, which will cause a large amount of silica sol to be lost during the preparation process. By comparing the data, it can be found that the tensile strength and impact strength of Example 1 are greatly improved compared with Comparative Example 1, and the same is true for the tensile strength after fire and the impact strength after fire.
[0082] Compared with Comparative Example 2, Example 1 adds porcelain-forming fillers and glass powder. Since the porcelain-forming fillers and glass powder can be porcelainized under the high temperature environment of flame, it can be found that the tensile strength and impact strength of the ceramic fiber board of Example 1 after burning decrease less than those before burning. However, since the ceramic fiber board of Comparative Example 2 does not contain porcelain-forming fillers and glass powder, its tensile strength and impact strength after burning decrease more than those before burning.
[0083] Example 2 (Double-layer fumed silica layer) (I) Preparation of ceramic fibers coated with a fumed silica layer by chemical vapor deposition (CVD): S1: Place the high-aluminum aluminum silicate ceramic fiber in the reaction chamber of the CVD chamber and introduce oxygen. First, adjust the temperature of the reaction chamber to 250°C and the pressure to normal pressure.
[0084] S2: Ethyl orthosilicate and silane are introduced into the reaction chamber at the same time (the flow ratio of ethyl orthosilicate to oxygen is 2 / 3:1, and the flow ratio of silane to oxygen is 1.25:1). At this time, the temperature of the reaction chamber is 250°C and the pressure is normal pressure. Under the above temperature and pressure, gaseous silane reaches the reaction temperature first, and after the reaction, a gas-phase silica inner layer is formed on the surface of the ceramic fiber; the reaction time is 10 minutes. After the reaction is completed, stop passing silane, adjust the temperature of the reaction chamber to 700°C and the pressure to 10 2 Pa; under the above temperature and pressure, ethyl orthosilicate begins to react, the reaction time is 5 minutes, and after the reaction, an outer layer of fumed silica is formed on the surface of the inner layer of fumed silica; wherein the outer layer of fumed silica is looser and more porous than the inner layer of fumed silica.
[0085] S3: After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0086] (II) Preparation of high temperature resistant ceramic fiberboard: S1: Add 2000 g of water to a ball mill, add 7 g of ceramic fiber coated with a fumed silica layer, adjust the pH to 9, and disperse at high speed (dispersion speed is 2000 r / min, time is 90 min).
[0087] S2: Add 3.5g of wollastonite as a porcelain filler and 2.0g of glass powder (main components are 62.1wt% silicon oxide, 16wt% boron oxide, 12.5wt% titanium oxide, 8wt% zinc oxide, and 1.4wt% aluminum oxide), and stir evenly (stirring speed is 1000r / min, time is 5min).
[0088] S3: Add 0.05 g of aluminum sulfate as a flocculant and stir evenly (stirring speed is 1000 r / min, time is 5 min).
[0089] S4: pouring the obtained slurry into a mold for dehydration and molding.
[0090] S5: hot pressing and drying the obtained molding material (the pressing and drying temperature is 150° C. and the time is 3 minutes) to obtain a high temperature resistant ceramic fiberboard.
[0091] Example 3 The only difference between Example 3 and Example 2 is that when depositing the outer layer of fumed silica, the amount of ethyl orthosilicate introduced is too high. The specific steps are as follows: S1: Place the high-aluminum aluminum silicate ceramic fiber in the reaction chamber of the CVD chamber and introduce oxygen. First, adjust the temperature of the reaction chamber to 250°C and the pressure to normal pressure.
[0092] S2: Ethyl orthosilicate and silane are introduced into the reaction chamber at the same time (the flow ratio of ethyl orthosilicate to oxygen is 1.25:1, and the flow ratio of silane to oxygen is 1.25:1). At this time, the temperature of the reaction chamber is 250°C and the pressure is normal pressure. Under the above temperature and pressure, gaseous silane reaches the reaction temperature first, and after the reaction, a gas-phase silica inner layer is formed on the surface of the ceramic fiber; the reaction time is 10 minutes. After the reaction is completed, stop passing silane, adjust the temperature of the reaction chamber to 700°C and the pressure to 10 2 Pa; under the above temperature and pressure, ethyl orthosilicate begins to react for 5 minutes, and after the reaction, an outer layer of fumed silica is formed on the surface of the inner layer of fumed silica.
[0093] S3: After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0094] Example 4 The only difference between Example 4 and Example 2 is that when depositing the outer layer of fumed silica, the amount of ethyl orthosilicate introduced is too low. The specific steps are as follows: S1: Place the high-aluminum aluminum silicate ceramic fiber in the reaction chamber of the CVD chamber and introduce oxygen. First, adjust the temperature of the reaction chamber to 250°C and the pressure to normal pressure.
[0095] S2: Ethyl orthosilicate and silane are introduced into the reaction chamber at the same time (the flow ratio of ethyl orthosilicate to oxygen is 1 / 3:1, and the flow ratio of silane to oxygen is 1.25:1). At this time, the temperature of the reaction chamber is 250°C and the pressure is normal pressure. Under the above temperature and pressure, gaseous silane reaches the reaction temperature first, and after the reaction, a gas-phase silica inner layer is formed on the surface of the ceramic fiber; the reaction time is 10 minutes. After the reaction is completed, stop passing silane, adjust the temperature of the reaction chamber to 700°C and the pressure to 10 2 Pa; under the above temperature and pressure, ethyl orthosilicate begins to react for 5 minutes, and after the reaction, an outer layer of fumed silica is formed on the surface of the inner layer of fumed silica.
[0096] S3: After the reaction is completed, the gas is stopped and the reaction chamber is restored to atmospheric pressure to end the chemical vapor deposition. The product can then be taken out of the reaction chamber, cleaned to remove by-products and impurities, and dried to obtain a ceramic fiber with a gas-phase silica layer on the surface.
[0097] Performance Testing The performance of the high temperature resistant ceramic fiberboards prepared in Examples 2-4 was tested using the same testing method as above. The test results are shown in the following table: From the comparison of the data in the above table, we can see that: Compared with Example 1, Example 2 has two different layers of fumed silica layers pre-deposited on the surface of the ceramic fiber. Through data comparison, it can be found that the strength of the ceramic fiber board of Example 1 before burning is not much different from that of Example 2, but the strength after burning is significantly reduced compared with Example 2. The main reason is that the second porous fumed silica layer (the outer layer of fumed silica) is looser and more porous, and the colloid viscosity formed after meeting water is higher, which can significantly improve the retention rate of ceramic fillers and glass powder, so that the strength after burning is higher.
[0098] Compared with Example 2, the strength difference of the ceramic fiberboard before burning in Example 3 and Example 4 is smaller, but the strength drop after burning is significantly higher than that in Example 2. The reason is that if the flow rate of ethyl orthosilicate is too high (Example 3) or too low (Example 4), it will affect the deposition effect of the outer layer of fumed silica, and then affect the bonding effect of ceramic fiber and other powders. However, compared with Example 1, the comprehensive effect of Example 3 and Example 4 is better.
[0099] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A high temperature resistant ceramic fiberboard, characterized in that: The invention comprises the following raw materials in parts by weight: 30-70 parts of ceramic fiber coated with fumed silica layer on the surface, 20-50 parts of porcelain filler, Glass powder 10-30 parts, Flocculant 0.05-1 part, water.
2. The high temperature resistant ceramic fiberboard according to claim 1, characterized in that: The fumed silicon dioxide layer is formed by in-situ oxidation of ethyl orthosilicate and / or silane on the surface of the ceramic fiber through a chemical vapor deposition method.
3. The high temperature resistant ceramic fiberboard according to claim 1 or 2, characterized in that: The ceramic fiber is one or more of aluminum silicate fiber, aluminum oxide fiber, mullite fiber, quartz fiber, silicon carbide fiber, zirconium oxide fiber and nitride fiber; The porcelain-forming filler is one or more of wollastonite, diatomaceous earth, kaolin, calcium carbonate and mica powder; The glass powder is one or more of silicon oxide, boron oxide and metal oxide; The flocculant is one or more of polyacrylamide, polyethyleneimine, aluminum sulfate, ferric sulfate and polyaluminum chloride.
4. A method for preparing a high temperature resistant ceramic fiberboard according to any one of claims 1 to 3, characterized in that The following steps are involved: S1: adding ceramic fibers coated with a fumed silica layer into water, adjusting to alkalinity, and dispersing; S2: Add porcelain filler and glass powder and stir well; S3: Add flocculant and stir well; S4: pouring the obtained slurry into a mold for dehydration and forming; S5: hot pressing and drying the obtained molding material to obtain a high temperature resistant ceramic fiberboard.
5. The preparation method according to claim 4, characterized in that: The preparation method of the ceramic fiber having a fumed silica layer coated on the surface comprises: 1) Place the ceramic fiber in the reaction chamber and introduce oxygen; 2) Ethyl orthosilicate or silane is introduced into the reaction chamber, and after reaction, it reacts on the surface of the ceramic fiber to form a fumed silica layer.
6. The preparation method according to claim 5, characterized in that: In step 1), the temperature of the reaction chamber is adjusted to 200-1000°C and the pressure is adjusted to 10 2 -10 5 Pa.
7. The preparation method according to claim 5, characterized in that: In step 2), the flow ratio of ethyl orthosilicate or silane to oxygen is 2 / 3-2:1, and the reaction time is 5-30 minutes.
8. The preparation method according to claim 4, characterized in that: In S1, the dispersion speed is 1000-3000 r / min, the time is 60-120 min, and the solution pH is 8-10.
9. The preparation method according to claim 4, characterized in that: In S2, the stirring speed is 300-2000 r / min and the time is 2-10 min.
10. The preparation method according to claim 4, characterized in that: In S3, the stirring speed is 300-2000 r / min, and the time is 1-5 min; in S5, the temperature of hot pressing and drying is 120-180°C, and the time is 1-5 min.
Citation Information
Patent Citations
Silicon dioxide heat insulator and preparation method thereof
CN101671158A
High-strength slag-falling-resistant ceramic fiber board and preparation method thereof
CN114315398A
High-temperature-resistant ceramic fiber board and preparation method thereof
CN118754653A
Prep. of preparing fiber reinforced silica-base composite material
CN1448369A
Method of fabricating a ceramic matrix composite for resistance against silicon attack
US11731910B1
Cited By
Quartz reinforced calcium silicate fiberboard and preparation method thereof
CN122520433A